SHAMSU-L-AIMMA SARAHSI'S WORK "MABSUT" EXPLORATION OF "SALAM" TRADE (Archive of Conferences, 2020)
Although Shamsu-l-aimma Sarahsi lived and worked in the 11th century AD, his work Mabsut is still widely studied in the field of Islamic jurisprudence. It is known that the most important part of the circulation of jurisprudence is the pre-sale part, that is, the rich book, and this article deals with the issues related to the sale of salam in this book.